2008
DOI: 10.1359/jbmr.080207
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Bodies Convey Activity Capable of Initiating Osteoclastogenesis and Localized Bone Destruction

Abstract: ABSTRACT:Introduction: Osteocyte apoptosis co-localizes with sites of osteoclastic bone resorption in vivo, but to date, no causal molecular or signaling link has been identified between these two processes. Materials and Methods: Osteocyte apoptotic bodies (OABs) derived from the MLO-Y4 osteocyte-like cell line and primary murine osteocytes and apoptotic bodies (ABs) derived from primary murine osteoblasts were introduced onto the right parietal bone of murine calvariae, and osteoclastic bone resorption was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
117
2
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 60 publications
10
117
2
12
Order By: Relevance
“…In line with this, others have reported that the proosteoclastogenic effect of apoptotic bodies derived from osteocytes is independent of RANKL. 19 Furthermore, our in vitro findings were confirmed by our ex vivo immunohistochemistry data showing the lack of RANKL expression in the bone biopsy osteocytes. We also found that the pro-osteoclastogenic factor CCL3 5 --7 was not expressed by HOB-01 cells, but it was upregulated in the HMCLs cocultured with preosteocytes, and it was involved in the pro-osteoclastogenic effect of the CM, thus suggesting that MM cell CCL3 production is increased in the presence of osteocytes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with this, others have reported that the proosteoclastogenic effect of apoptotic bodies derived from osteocytes is independent of RANKL. 19 Furthermore, our in vitro findings were confirmed by our ex vivo immunohistochemistry data showing the lack of RANKL expression in the bone biopsy osteocytes. We also found that the pro-osteoclastogenic factor CCL3 5 --7 was not expressed by HOB-01 cells, but it was upregulated in the HMCLs cocultured with preosteocytes, and it was involved in the pro-osteoclastogenic effect of the CM, thus suggesting that MM cell CCL3 production is increased in the presence of osteocytes.…”
Section: Discussionsupporting
confidence: 77%
“…18,19 Interestingly, the role of osteocyte death has also been demonstrated in pathophysiological conditions characterized by a high rate of bone resorption, such as estrogen deficiency, 22,23 aging 28 and glucorticoid-induced osteoporosis, 24,25 and our current findings show that osteocyte death may have a role in MM-induced osteoclastogenesis and bone disease. The potential in vivo role of osteocytes in MM bone disease was investigated by determining osteocyte viability in bone biopsy samples obtained from MM patients and controls.…”
Section: Discussionsupporting
confidence: 70%
“…[19][20][21] The ubiquity and abundance of osteocytes is further testament to their importance: they are extremely numerous (between 30 000 and 90 000 cells per cubic mm, and representing 90-95% of all bone cells), can be very long-lived (up to several decades in humans) and have been found in all investigated species of tetrapods (amphibians, reptiles, birds and mammals; Figures 1a-d). 22,23 It is therefore thoughtprovoking that the entire skeleton of many fishes-in particular the advanced teleost fishes, which represent at least 50% of the bony vertebrate species-consists entirely of bone material that does not contain osteocytes. This observation raises the intriguing question of how the skeleton of these animals accomplishes the various essential functions attributed to osteocytes in other vertebrates, and raises the possibility that in fish with anosteocytic bone, some of these functions are either accomplished by non-osteocytic routes or are not necessary at all.…”
mentioning
confidence: 99%
“…The possibility that osteocytes may regulate osteoclast formation has been suggested recently by the observation that RANKL may be released by osteocytes to initiate osteoclast formation after microfracture. (19) The lack of a coupling-associated increase in osteoclast surface even at a very high dose of PTH treatment in SOST null mice provides another link between the osteocyte and the osteoclast, suggesting intriguingly that inhibition of sclerostin is required for the link between increased osteoblast activity and osteoclast formation during PTH treatment.It has been reported recently that while PTH increases osteoblast number in trabecular bone by inhibiting osteoblast apoptosis, periosteal osteoblasts have a constitutively lower level of apoptosis. (20) This regional difference requires that PTH stimulate osteoblast number in cortical and trabecular bone through different mechanisms.…”
mentioning
confidence: 99%
“…The possibility that osteocytes may regulate osteoclast formation has been suggested recently by the observation that RANKL may be released by osteocytes to initiate osteoclast formation after microfracture. (19) The lack of a coupling-associated increase in osteoclast surface even at a very high dose of PTH treatment in SOST null mice provides another link between the osteocyte and the osteoclast, suggesting intriguingly that inhibition of sclerostin is required for the link between increased osteoblast activity and osteoclast formation during PTH treatment.…”
mentioning
confidence: 99%